Chinese Economic Activities in Sub Saharan Africa: A Substitute for Europe? - Keers, Ineke; Pennink, Bartjan J. W., Dr. (UI Scholars Hub, 2010)
This paper aims to investigate if the Chinese economic ties with Sub Saharan Africa serve as a substitute for this existing European-African relationship. Three types of economic activities are studied to determine a possible substitution effect: 1) trade (imports and exports) 2) foreign direct investment (FDI) flows; and 3) development aid from China and the European Union towards six African countries. Because natural resources, especially oil, appear to be a driver for Sino-African trade this study focuses on oil-importing and oil-exporting African countries. The group of oil-importing African countries is formed by South Africa, Ghana, and Kenya. The oil-producing countries are represented by Nigeria, Angola, and Sudan. We found that there is no Chinese FDI flows seem to be complementary rather than a substitute for each other, which then could lead to the development of African industries. Moreover, the combinantion of European and Chinese trade, aid and FDI could lead to the developmment of infrastructure, manufacturing industries, and the improvement of social-economical standards in Africa.